EFFORTS TO REDUCE THE RISK OF DEFECTS OF MINICAB PRODUCTS TYPE MSM 2230 IN ASSEMBLING PROCESS WITH FAILURE MODE EFFECT AND ANALYSIS METHOD - Huda, Nurul; Ismiyah, Elly; Fathoni, M. Zainuddin (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC); Vol 1 No 2 (2021): UMGCINMATIC : 1st Rethinking Education during Covid-19 Era: Challange and InnovationDO - 10.30587/umgeshic.v1i2.3435, 2021)
Indospring Tbk, is a spring producer company of two types, namely leaf springs and coil springs. Based on the results of the data obtained from the assembling process at PT. Indospring, Tbk that there are still high defects or product incompatibility, especially Minicab type MSM 2230 with 290 types of defects for 3 months (January 2021 - March 2021) with a percentage of 18.59%. The purpose of this research is to find out the types of Minicab MSM 2230 defects in the assembly line process, to find out the factors that cause defects problems, to provide benefits as knowledge and considerations to improve quality by correcting the causes of product defects. In finding the cause of product defects and their impact using the Failure Mode Effect and Analysis (FMEA) method. During the period from January to March 2021, before repairing the average defect, koba defects 17.33, scratch 20, eye forming defects 4.33, half span NG 15.33, eccentricity out spec 2, taper NG 11.66, pieces NG, 18 .66, EF gap narrowed 0.66, crack 6.66. Based on Failure Mode Effect Analysis, scratch has the highest Risk Priority Number value, which is 324 with a value of 9 on severity, 6 on occurrence and 6 on detection. The results of brainstorming factors that cause defect scratch, namely the product testing process is often dragged down due to speeding up the production flow, during the after tempering process the operator is wrong in the arrangement on the rack / pallet, and it can also be that the material from the supplier is already scratched. So that the highest defect will be the main priority for immediate repairs.